Effects of pharmacist-driven protocol on naloxone prescribing rates in two primary care clinics - Ashley Daffron; Kelly Koon; Nathan P Gruenke; Sara Wettergreen (Preventive Medicine Reports, 2023)
The Centers for Disease Control and Prevention (CDC) Guidelines for Prescribing Opioids for Chronic Pain recommend co-prescribing naloxone as a harm reduction strategy when there is an increased risk of opioid overdose. Although naloxone co-prescribing is an important harm reduction strategy, many at risk patients are not prescribed naloxone. The objective was to assess the effectiveness of a pharmacist-driven protocol at increasing the number of patients co-prescribed naloxone according to CDC recommendations. The study design was a multi-center retrospective cohort to evaluate the outcomes of a quality improvement intervention at two primary care clinics which aimed to increase naloxone co-prescribing. The intervention used a two-pronged approach consisting of telephonic outreach to eligible patients by pharmacists and pharmacy interns related to naloxone education and recommendations for naloxone co-prescribing. Additionally, recommendations were sent to the primary care provider in the electronic medical record (EMR) for consideration and implementation. After the 3 month intervention, 57 of the 86 patients contacted were co-prescribed naloxone (66.3%). Most naloxone initiation occurred at the time of telephonic outreach as a new medication order (n = 36), however an additional 12 patients were co-prescribed naloxone at a subsequent primary care provider visit. The proportion of patients at each clinic with MME ≥ 50 co-prescribed naloxone significantly increased after implementation of the intervention (pre 25/64 vs. post 43/76, p = 0.043). Overall, telephonic outreach to patients with recommendations to primary care providers in the EMR were effective methods to increase the rate of naloxone co-prescribing in primary care based on this study.